Pertumbuhan dan Produksi Tanaman Mentimun terhadap Pemberian Berbagai Takaran Vermikompos pada Tanah Podsolik Merah Kuning - Ahmad Nazarudin; Mahdiannoor; Zarmiyeni Zarmiyeni (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2019)
Cucumber plants, including vines, are popular with the wider community. Hulu Sungai Tengah Regency is dominated by red-yellow podzolic soil types which have problems such as sandy clay soil structure, low permeability, poor soil aeration, acidic reacting soil, water holding capacity, nutrients and low cation exchange capacity. The effort that can be done is by giving organic material produced from a mixture of earthworm media with earthworm feces. The purpose of this study (i) was to see the effect of vermicompost administration and (ii) to get the best dose of vermicompost administration on the growth and production of cucumber plants on red-yellow podzolic soil. This research was conducted in Teluk Mesjid Village, Haruyan District, Hulu Sungai Tengah District, South Kalimantan Province. This research was conducted in April-June 2015, using a single randomized block design (RBD), with five treatment levels and five groups so that there were 25 experimental units. The treatments that were tried were vermicompost doses namely (v0) 0 t.ha-1, (v1) 10 t.ha-1, (v2) 20 t.ha-1, (v3) 30 t.ha-1, and (v4 ) 40 t.ha-1. The variables observed were planting length, number of leaves, stem diameter, flowering time, number of fruits, and wet weight of fruit crops. The results showed the treatment had a significant effect on the stem diameter variable age 21 day after planting (DAP), flowering time, number of cucumber fruit, and had a very significant effect on the cucumber wet weight but did not affect plant length 7, 14 and 21 DAP, number of leaves aged 7, 14 and 21 DAP, stem diameter aged 7 and 14 DAP. The best treatment for vermicompost for cucumber plants is (v1) 10 t.ha-1.